Transcriptome‐wide Identification of RNA‐binding Protein Binding Sites Using Photoactivatable‐Ribonucleoside‐Enhanced Crosslinking Immunoprecipitation (PAR‐CLIP). Issue 1 (3rd April 2017) - Maatz, Henrike; Kolinski, Marcin; Hubner, Norbert; Landthaler, Markus
Abstract: RNA‐binding proteins (RBPs) mediate important co‐ and post‐transcriptional gene regulation by binding pre‐mRNA in a sequence‐ and/or structure‐specific manner. For a comprehensive understanding of RBP function, transcriptome‐wide mapping of the RNA‐binding sites is essential, and CLIP‐seq methods have been developed to elucidate protein/RNA interactions at high resolution. CLIP‐seq combines protein/RNA UV‐crosslinking with immunoprecipitation (CLIP) followed by high‐throughput sequencing of crosslinked RNA fragments. To overcome the limitations of low RNA‐protein crosslinking efficiency in standard CLIP‐seq, photoactivatable‐ribonucleoside‐enhanced CLIP (PAR‐CLIP) has been developed. Here, living cells or whole organisms are fed photo‐activatable nucleoside analogs that are incorporated into nascent RNA transcripts before UV treatment. This allows greater crosslinking efficiency at comparable radiation doses for enhanced RNA recovery and separation of crosslinked target RNA fragments from background RNA degradation products. Moreover, it facilitates the generation of specific UV‐induced mutations that mark the crosslinking nucleotide and allow transcriptome‐wide identification of RBP binding sites at single‐nucleotide resolution. © by 2017 John Wiley & Sons, Inc.